2020
DOI: 10.1021/acsearthspacechem.0c00008
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Kinetics and Equilibria for the Condensed Phase Reactions of Hydroperoxides with Carbonyls to Form Peroxyhemiacetals

Abstract: Heterogeneous/multiphase reactions can influence the formation, composition, and chemical–physical properties of secondary organic aerosol (SOA), but data describing their kinetics and equilibria remain sparse. Here, we synthesized and utilized a probe molecule to investigate the condensed phase reactions of hydroperoxides with ketones and aldehydes, including those in SOA generated from the ozonolysis of α-pinene in an environmental chamber. The probe molecule, which contained a hydroperoxide group and a UV-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…This chain reaction is terminated by reactions such as RO 2 + HO 2 and RO 2 + RO 2 , resulting in the formation of multifunctional peroxides . Another possible pathway for these alkenals to form peroxides is via OH-initiated H abstraction on the aldehyde group, which forms the peroxy acid. , Interactions between carbonyls and peroxides can further produce peroxyhemiacetals/ketals with lower volatilities, which may increase the gas-to-particle partitioning of organic peroxides . In summary, the significant peroxide content observed in SOA from heated cooking oil could be explained by the photooxidation of alkenals in our study.…”
Section: Resultsmentioning
confidence: 99%
“…This chain reaction is terminated by reactions such as RO 2 + HO 2 and RO 2 + RO 2 , resulting in the formation of multifunctional peroxides . Another possible pathway for these alkenals to form peroxides is via OH-initiated H abstraction on the aldehyde group, which forms the peroxy acid. , Interactions between carbonyls and peroxides can further produce peroxyhemiacetals/ketals with lower volatilities, which may increase the gas-to-particle partitioning of organic peroxides . In summary, the significant peroxide content observed in SOA from heated cooking oil could be explained by the photooxidation of alkenals in our study.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that ambient SOA particles can bounce off from an impactor stage depending on ambient conditions, indicating non-liquid states of organic particles (Virtanen et al, 2011;Bateman et al, 2017;Slade et al, 2019). Measurements of the viscosity of SOA bulk materials derived from the oxidation of limonene (Hinks et al, 2016), toluene (Song et al, 2016), α-pinene (Renbaum-Wolff et al, 2013;Kidd et al, 2014;Bateman et al, 2015;Zhang et al, 2015;Grayson et al, 2016;Hosny et al, 2016) and isoprene (Song et al, 2015) have confirmed that viscosity of SOA particles can vary depending on temperature and RH . In addition, previous studies have shown that SOA chemical composition can be affected by experimental conditions upon SOA formation such as RH and particle mass concentrations (Kidd et al, 2014;Hinks et al, 2018;Grayson et al, 2016;Jain et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Figure 5. Simulated functional group distributions in particle-phase compounds derived from isoprene photooxidation (Song et al, 2015) and α-pinene ozonolysis (Bateman et al, 2015;Kidd et al, 2014;Grayson et al, 2016;Zhang et al, 2015;Renbaum-Wolff et al, 2013). sons for the discrepancies between measurements and simulations of SOA viscosity.…”
Section: Chemical Composition and Functional Group Distributions Of Soamentioning
confidence: 99%
“…Chemical composition simulated for Zhang's experiments is characterized by the highest -RCHO fraction among all experiments, which may explain the largest difference between predicted and measured viscosities. Aldehydes are known to be highly reactive in the condensed phase by reacting with alcohols and hydroperoxides to form peroxyhemiacetals and oligomers (Ziemann and Atkinson, 2012) Such multiphase reactions could be accelerated under acidic conditions in the presence of carboxylic acids (Bakker-Arkema and Ziemann, 2020;Shiraiwa et al, 2013 Bateman et al, 2015Kidd et al, 2014Grayson et al, 2016Zhang et al, 2015Renbaum-Wolff et al, 2013 Figure 5. Simulated functional group distributions in particle-phase compounds derived from α-pinene ozonolysis for various experiments.…”
Section: Chemical Composition and Functional Group Distributions Of Soamentioning
confidence: 99%